Resistance to gastro-intestinal parasites in Dorper and Red Maasai-Dorper crossbred sheep - Reynolds, L.; Baker, R.L.; Sherington, J.; Njubi, D. (Small Ruminant Collaborative Research Support Program, 1992)
Studies the within-and between-breed differences in resistance to natural infection with gastro-intestinal parasites and identifies genetic markers to aid in the selection of animals. Data analysed include PCV (Packed Cell Volume), live weight from birth to 360 days and faecal egg counts.